2019
DOI: 10.1242/dev.178871
|View full text |Cite|
|
Sign up to set email alerts
|

Nutrient restriction causes reversible G2 arrest in Xenopus neural progenitors

Abstract: In the Materials and Methods section, the concentration of rapamycin used was incorrect. Corrected: mTOR was blocked with a bath solution containing 10 µM rapamycin (Sigma-Aldrich) diluted in rearing media for up to 48 h. Original: mTOR was blocked with a bath solution containing 10 mM rapamycin (Sigma-Aldrich) diluted in rearing media for up to 48 h. Both the online full-text and PDF versions have been updated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 103 publications
2
7
0
Order By: Relevance
“…Cell cycle delay is further supported by the observation that contrary to overall Sox2 positive cell number, the number of transfected, Sox2-positive cells in chicken embryos was increased relative to controls. In agreement with our findings, nutrient restriction was shown to arrest the proliferation of neural progenitors of Xenopus larvae and zebrafish reversibly in G2, suggesting that most of the cells were quiescent( 32 ). While arrest did not require mTOR signaling, nutrient dependent cell cycle reentry was mTOR dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Cell cycle delay is further supported by the observation that contrary to overall Sox2 positive cell number, the number of transfected, Sox2-positive cells in chicken embryos was increased relative to controls. In agreement with our findings, nutrient restriction was shown to arrest the proliferation of neural progenitors of Xenopus larvae and zebrafish reversibly in G2, suggesting that most of the cells were quiescent( 32 ). While arrest did not require mTOR signaling, nutrient dependent cell cycle reentry was mTOR dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Cell cycle delay was further supported by the observation that, contrary to overall Sox2 positive cell numbers, the number of transfected, Sox2-positive cells in chicken embryos was increased relative to controls. In agreement with our findings, nutrient restriction was shown to arrest the proliferation of neural progenitors of Xenopus larvae and zebrafish reversibly in G2, suggesting that most of the cells were quiescent (43), consistent with the lack of evidence for cell death or senescence in ADSL depleted systems. While arrest in Xenopus progenitors did not require mTOR signaling, nutrient dependent cell cycle reentry was mTOR dependent.…”
Section: Discussionsupporting
confidence: 92%
“…Pedersen, 1970). Recent studies in Drosophila , Xenopus Laevis and C. elegans tissues uncovered that populations of adult stem cells are halted in G2-phase and can be triggered to divide by growth factor and nutrient signaling (McKeown and Cline, 2019; Morris and Spradling, 2011; Otsuki and Brand, 2018; Seidel and Kimble, 2015; Zielke et al, 2014). Extrinsic control of G2/M progression may thus be a widely conserved element of the eukaryotic cell cycle.…”
Section: Discussionmentioning
confidence: 99%
“…The division rate of these cells is presumed to be independent of external regulation, as it has been a prevailing dogma that following G1/S transition, progression through the cell cycle becomes irresponsive to extrinsic cues (Pardee, 1989). However, recent findings in invertebrate germline and neural stem cells revealed that progression through later cell cycle stages can be modulated by nutrient signaling (McKeown and Cline, 2019; Otsuki and Brand, 2018; Seidel and Kimble, 2015). Yet, how extrinsic signals influence progression through later stages of the cell cycle and thereby the rate of cell division in epithelia is not well understood.…”
Section: Introductionmentioning
confidence: 99%